ANÁLISIS Y PROPUESTA DIDÁCTICA PARA MEJORAR LA COMPRENSIÓN LECTORA EN EL MANUAL DE PUERTAS ABIERTAS (3.ER CURSO) - Saida Bedarnia; Mebarka Bedarnia (Studii de gramatică contrastivă)
This study analyses the treatment of reading comprehension in the Puertas Abiertas textbook for 3rd-year secondary school, used in teaching Spanish as a foreign language (ELE) in Algeria. Our primary objective is to design a set of activities focused on reading comprehension items to enhance the treatment of this key skill. To achieve this, we selected the reading sequence from the textbook as the corpus and structured the research under a mixed-methods approach (quantitative and qualitative),a projective framework, with a non-experimental design and a comprehensive level of analysis. We employed descriptive and analytical methods, supported by tools such as a content analysis grid, rubrics, document analysis, and a questionnaire aimed at secondary school teachers. The results revealed that most reading comprehension questions are limited to the literal level, with items at lower cognitive levels. The predominant textual typology is expository-argumentative, while the selected texts cover a variety of engaging topics. Based on these findings, we propose a pedagogical design grounded in Bloom's Taxonomy (focusing on higher cognitive levels), Cassany's approach, and the interactive model, aiming to enrich the teaching of reading comprehension in this educational context.